Phage biocontrol to combat Pseudomonas syringae pathogens causing disease in cherry. Issue 5 (8th May 2020) - Rabiey, Mojgan; Roy, Shyamali R.; Holtappels, Dominique; Franceschetti, Linda; Quilty, Billy J.; Creeth, Ryan; Sundin, George W.; Wagemans, Jeroen; Lavigne, Rob; Jackson, Robert W.
Summary: Bacterial canker is a major disease of Prunus species, such as cherry ( Prunus avium ). It is caused by Pseudomonas syringae pathovars, including P. syringae pv. syringae ( Pss ) and P. syringae pv. morsprunorum race 1 ( Psm1 ) and race 2 ( Psm2 ). Concerns over the environmental impact of, and the development of bacterial resistance to, traditional copper controls calls for new approaches to disease management. Bacteriophage‐based biocontrol could provide a sustainable and natural alternative approach to combat bacterial pathogens. Therefore, seventy phages were isolated from soil, leaf and bark of cherry trees in six locations in the south east of England. Subsequently, their host range was assessed against strains of Pss, Psm1 and Psm2 . While these phages lysed different Pss, Psm and some other P. syringae pathovar isolates, they did not infect beneficial bacteria such as Pseudomonas fluorescens . A subset of thirteen phages were further characterized by genome sequencing, revealing five distinct clades in which the phages could be clustered. No known toxins or lysogeny‐associated genes could be identified. Using bioassays, selected phages could effectively reduce disease progression in vivo, both individually and in cocktails, reinforcing their potential as biocontrol agents in agriculture. Abstract : This study demonstrates a comprehensive analysis combining multiple elements that are significant for application of a bacteriophage as a potential biological control of bacterial canker of cherry. Bacteriophages were isolated from wide range of samples in cherry orchards in the UK. The phages had specific host range, with some able to lyse three strains of Pss, Psm1 and Psm2, causative agents of canker in cherry with an observed impact in reducing bacterial counts. Stability of the phages were tested at a range of different temperatures over a six‐month period and revealed they were capable of surviving in different environmental temperatures typical of the annual weather variations in the UK, which is a significant factor in choosing a phage for biocontrol. The phages could effectively reduce bacterial disease progression and infectivity in different plant systems. Genome sequencing of the bacteriophages revealed their novelty and divided the phages into five distinct clades, belonging to three different families, with no known toxins or lysogeny associated genes which indicate their use as an environmentally friendly biocontrol agent in cherry industry.